Women on Boards of Philippine Corporations: Quantitative Explorations - Maria Cristina G. Bautista; Marlene M. De Leon; Rudyard Jose R. Nano IV (International Journal of Business and Society, 2020)
This inductive study explored the likelihood and correlates of gender diversity in corporate boards in the Philippines. The improvement of gender diversity on boards is of advocacy and policy interest as the country emergesto middle-high income status. Logistic regression analyses from individuals’ (in a directors’ talent pool) responses to an online survey showed that females had a likely odds of 0.10 to be on the boards, compared to males. For every one female getting onto boards, 9 would be unable to.Females with advanced degrees were 7x likely to be on boards than female and male counterparts. The odds of a board seat is significantly likely for individuals in some industries compared to a referent industry (government). At the firm level, controlling other variables in the model, as the size of boards are increased by a unit, the odds of having a woman on board increase 1.3 times.This implies that the likelihood of having a woman board of director rises if the size of boards is raised by a third. Corroboration from text mining technique applied to survey responses showed strong correlation across academic degrees (both bachelor’s and advanced), industry, and job title; pointing that having more women in C-roles increase the odds of increasing their numbers on corporate boards. Gender diversity on boards have been studied largely fromthedeveloped economy lens and/or international comparisons. These quantitative explorations showed pathways that can advance not only understanding and support for extant theories (human capital, resource dependence), but also point to further work (institutional, industry) that can provide levers for policy and advocacy, for countries with similar challenges.